2007
DOI: 10.1038/sj.npp.1301470
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Sensitivity to Stress and Drug/Alcohol Craving in Abstinent Cocaine-Dependent Individuals Compared to Social Drinkers

Abstract: Chronic exposure to cocaine is associated with neuroadaptions in stress and reward circuits that may increase susceptibility to relapse. We examined whether there are alterations in stress response and craving in abstinent cocaine-dependent individuals compared with a demographically matched group of non-addicted socially drinking community controls. Forty treatment-engaged abstinent cocaine patients (17F/23M) and 40 controls (19F/21M) were exposed to a brief 5 min guided imagery of individually calibrated str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
166
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 165 publications
(183 citation statements)
references
References 61 publications
16
166
1
Order By: Relevance
“…The importance of the alteration of such mechanisms is reinforced by the evidence that all these alterations occurred without changes in the circulating levels of glucocorticoids, although we cannot exclude that the hormonal levels might have been altered at different time points. Of note, the effects produced by short withdrawal wane in animals abstinent for 48 days, indicating that they are peculiar of the short-term withdrawal, an observation that might be of functional relevance given the altered response to stress observed in cocaine users during early abstinence (Fox et al, 2008;Sinha et al, 2003). Further, since we have previously shown that short-term withdrawal from developmental cocaine exposure causes an abnormal response to a stress challenge leading to pro-depressive symptoms (Caffino et al, 2015), we suggest that the herein shown dysregulation of the GR system may contribute to the negative emotional state observed in humans during early periods of abstinence (Gould, 2010;Koob, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of the alteration of such mechanisms is reinforced by the evidence that all these alterations occurred without changes in the circulating levels of glucocorticoids, although we cannot exclude that the hormonal levels might have been altered at different time points. Of note, the effects produced by short withdrawal wane in animals abstinent for 48 days, indicating that they are peculiar of the short-term withdrawal, an observation that might be of functional relevance given the altered response to stress observed in cocaine users during early abstinence (Fox et al, 2008;Sinha et al, 2003). Further, since we have previously shown that short-term withdrawal from developmental cocaine exposure causes an abnormal response to a stress challenge leading to pro-depressive symptoms (Caffino et al, 2015), we suggest that the herein shown dysregulation of the GR system may contribute to the negative emotional state observed in humans during early periods of abstinence (Gould, 2010;Koob, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Craving has become a subject of great interest as it is a reliable intermediate phenotype of relapse and the most distressing and long-lasting symptom experienced by dependent individuals between uses. Indeed, even after a period of abstinence, dependent individuals remain vulnerable to stress and other craving-inducing stimuli [10], which, in turn, leads to intense physiological responses and various negative feelings such as anger and sadness [11]. Real-time daily monitoring of craving and drug use has shown that craving reliably predicts relapse among dependent individuals [9,[12][13][14][15].…”
Section: Overview Of Addiction and Current Treatment Challengesmentioning
confidence: 99%
“…It remains to be determined if these properties translate in the attenuation of symptoms for other anxiety disorders than social phobia (e.g., post-traumatic stress disorder, panic disorder) [66]. There are contradictory results as to CBD's effect on sleep (similar to results from animal studies) as it has been associated with both wake-inducing and hypnotic properties in humans [11,67,68]. Altogether, many pharmacological, preclinical, and clinical properties (e.g., antipsychotic, anxiolytic) of CBD that had been demonstrated over roughly the last decade all point towards a potential role for CBD in alleviating behaviors relevant to addiction disorder.…”
Section: Cbd and Neurobiological Targets/effectsmentioning
confidence: 99%
“…mGluR 2/3 are located pre-, peri-, and post-synaptically (Benarroch, 2008), and negatively modulate glutamate transmission by inhibiting glutamate release and reducing neural excitability at the postsynaptic level (Ferraguti and Shigemoto, 2006;Pinheiro and Mulle, 2008;Schoepp, 2001). mGluR 2/3 are widely expressed throughout brain circuits that mediate ethanolassociated conditioned reinforcement, incentive motivation and reward (Dayas et al, 2007;Kenny and Markou, 2004;Tzschentke and Schmidt, 2003;Zhao et al, 2006), as well as circuits mediating stress and anxiety responses (Benarroch, 2008;Dayas et al, 2007;Zhao et al, 2006), the latter representing important risk factors for ethanol abuse and relapse (Brown et al, 1995;Fox et al, 2007Fox et al, , 2008; Kreek and Koob, 1998;Sinha, 2000Sinha, , 2001Sinha et al, 2009). Recent findings provide strong evidence that mGluR 2/3 participate in mediating many addiction-relevant actions of ethanol.…”
Section: Introductionmentioning
confidence: 99%